Infliximab and newly diagnosed neoplasia in Crohn's disease: a multicentre matched pair study. Issue 2 (24th August 2005) - Biancone, L; Orlando, A; Kohn, A; Colombo, E; Sostegni, R; Angelucci, E; Rizzello, F; Castiglione, F; Benazzato, L; Papi, C; Meucci, G; Riegler, G; et al.
Abstract : Background and aims: The widespread use of anti-tumour necrosis factor α antibody (Infliximab) in Crohn's disease (CD) raises concerns about a possible cancer risk in the long term. In a matched pair study, we assessed whether Infliximab is associated with an increased risk of neoplasia. Methods: In a multicentre matched pair study, 404 CD patients treated with Infliximab (CD-IFX) were matched with 404 CD patients who had never received Infliximab (CD-C). Cases and controls were matched for sex, age (±5 years), site of CD, age at diagnosis (±5 years), immunosuppressant use, and follow up. New diagnoses of neoplasia from April 1999 to October 2004 were recorded. Results: Among the 404 CD-IFX, neoplasia was diagnosed in nine patients (2.22%) while among the 404 CD-C, seven patients developed neoplasia (1.73%) (odds ratio 1.33 (95% confidence interval 0.46–3.84); p = 0.40). The survival curve adjusted for patient year of follow up showed no differences between CD-IFX and CD-C (p = 0.90; log rank test). In the CD-IFX group, there was one cholangiocarcinoma, three breast cancers, one skin cancer, one leukaemia, one laryngeal cancer, and two anal carcinomas. Among the 7/404 (1.73%) CD-C, there were three intestinal adenocarcinomas (two caecum, one rectum), one basalioma, one spinalioma, one non-Hodgkin's lymphoma, and one breast cancer. Age at diagnosis of neoplasia did not differ between groups (CD-IFX v CD-C: median 50 (range 40–70 years) v 45 (27–72); p = 0.50). Conclusion: In our multicentre matched pair study, the frequency of a new diagnosis of neoplasia in CD patients treated with Infliximab was comparable with CD patients who had never received Infliximab.